Anthropometry-Based Work Facility Design for the Paperbag Folding and Gluing Process (Case Study: UD XYZ) - Sabila Arifah Chafshoh; Handy Febri Satoto (Telkom University, 2026)
The folding and gluing process of paperbag production at UD XYZ is still carried out manually, with workers sitting on the floor without work facilities such as tables and chairs. This condition requires workers to adjust their body posture to the work object positioned at a low level, which may cause discomfort during work. This study aims to design ergonomic work facilities in the form of a work table and chair for the folding and gluing process using an anthropometric approach. Anthropometric data were collected from 31 workers in the folding and gluing section, including knee height, buttock-popliteal length, hip breadth, sitting elbow height, sitting shoulder height, shoulder breadth, and forward arm reach. The data were processed through mean calculation, standard deviation calculation, data adequacy test, data uniformity test, and percentile calculation. The results showed that the proposed work chair dimensions consisted of a chair height of 41 cm, seat depth of 46 cm, seat width of 38 cm, backrest height of 51 cm, and backrest width of 42 cm. The proposed work table was designed with a height of 65 cm, depth of 60 cm, and length of 120 cm. The proposed workstation is expected to improve posture suitability and reduce the potential risk of musculoskeletal discomfort during repetitive folding and gluing activities. The study contributes to ergonomic workstation design for labor-intensive SMEs through task-specific anthropometric adaptation